An Exploration of the Psychometric Properties of the PASS-20 in Older Adults with Chronic Pain: Preliminary Development and Validity. Issue 3 (27th May 2022) - Alonso-Fernández, Miriam; Gillanders, David; López-López, Almudena; Matías, Borja; Losada, Andres; González, José Luis
ABSTRACT: Objectives: The Pain Anxiety Symptoms Scale (PASS-20) is well validated in adults and younger populations, but not in older adults. This study aimed to analyze the psychometric properties of the PASS-20 in Spanish older adults who experience chronic pain. Methods: Participants were 111 older adults with chronic pain living in nursing homes (mean age = 83.36; SD = 6.53; 78.6% female). Face-to-face interviews were conducted which included assessment of pain anxiety (PASS-20), chronic pain acceptance (CPAQ), depression symptoms (GDS), catastrophizing beliefs (PCS), pain severity, and sociodemographic information. An Exploratory Structural Equation Modeling (ESEM) approach was used to refine the scale. Results: The final scale was composed of seven items, measuring two factors that could be labeled "Internal experiences" and "Escape/Avoidance behaviors". The two factors explained 60.98% of the total variance. PASS-7 version fit properly: χ 2 /df = 14.57/13, CMIN/df = 1.121, CFI = 0.99, RMSEA = 0.033, TLI = 0.98, GFI = 0.96, AGFI = 0.92. Good validity indices were found and acceptable reliability results in the scale and its subscales (Chronbach´s α; Internal Experiences = 0.70; Escape/Avoidance Behaviors= 0.73; Total Scale = 0.77). Conclusions: The short version of the PASS-7 has good psychometric properties. Clinical Implications: The brevity of the PASS-7 increases the feasibility of this instrument which could potentially be utilized in a variety of clinical settings and research studies with older people with chronic pain samples, specially institutionalized older adults.